2000
DOI: 10.1097/00043764-200008000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Knee Disorders in Floor Layers and Carpenters

Abstract: Previous studies indicate an increased prevalence of knee disorders in some occupations possibly related to kneeling working positions. The purpose of the present study was to examine the relationship among knee-straining work, self-reported knee-complaints, and physical signs of knee disorders. The duration of knee-straining work was estimated from videotapes of representative work tasks. Floor layers (n = 133), carpenters (n = 506), and compositors (n = 327) aged 26 to 72 years without previous acute knee tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
15

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 13 publications
2
49
0
15
Order By: Relevance
“…This study also revealed that brick field workers felt discomfort in their knees due to kneeling for a prolonged period of time during molding, during loading and unloading the mud and bricks, and while setting the green bricks in the kiln. Jensen et al support this result [16]. According to them, the prevalence of knee disorders in some occupations was possibly related to kneeling working postures.…”
Section: Discussionmentioning
confidence: 88%
“…This study also revealed that brick field workers felt discomfort in their knees due to kneeling for a prolonged period of time during molding, during loading and unloading the mud and bricks, and while setting the green bricks in the kiln. Jensen et al support this result [16]. According to them, the prevalence of knee disorders in some occupations was possibly related to kneeling working postures.…”
Section: Discussionmentioning
confidence: 88%
“…Jensen, Mikkelsen, Loft, et al support this result [13]. According to Jensen et al, prevalence of knee disorders in some occupations was possibly related to kneeling working postures [13].…”
Section: Discussionmentioning
confidence: 92%
“…Knee disorders produce costly disability to construction workers and result in their early departure from work [1,2]. Carpenters are one of the most common trades in the construction industry that have experienced this specific misfortune.…”
Section: Introductionmentioning
confidence: 99%
“…Carpenters are one of the most common trades in the construction industry that have experienced this specific misfortune. In particular, floor and carpet layers, some of whom belong to the United Brotherhood of Carpenters and Joiners of America [3], usually spend a great amount of their working time in knee-straining positions, including kneeling, knee-supporting (weight-bearing on the knees), and squatting [2,[4][5][6]. In addition to prolonged and awkward knee postures, the repetitive operation of the knee-kicker causes a great direct impact to the knee joint [7,8].…”
Section: Introductionmentioning
confidence: 99%